Development of Linguistic Linked Open Data Resources for Collaborative Data-Intensive Research in the Language Sciences - Pareja-Lora, Antonio; Lust, Barbara; Blume, Maria; Chiarcos, Christian (The MIT Press, 2019)
This book is the product of an international workshop dedicated to addressing data accessibility in the linguistics field. It is therefore vital to the book's mission that its content be open access. Linguistics as a field remains behind many others as far as data management and accessibility strategies. The problem is particularly acute in the subfield of language acquisition, where international linguistic sound files are needed for reference. Linguists' concerns are very much tied to amount of information accumulated by individual researchers over the years that remains fragmented and inaccessible to the larger community. These concerns are shared by other fields, but linguistics to date has seen few efforts at addressing them. This collection, undertaken by a range of leading experts in the field, represents a big step forward. Its international scope and interdisciplinary combination of scholars/librarians/data consultants will provide an important contribution to the field.